Interfaces for collecting data from patients: 10 golden rules. (16th January 2020) - Vickers, Andrew J; Chen, Ling Y; Stetson, Peter D
Abstract: Memorial Sloan Kettering Cancer Center has more than a decade's experience creating online interfaces for obtaining data from patients as part of routine clinical care. We have developed a set of "golden rules" for design of these interfaces. Many relate to the knowledge imbalance between professional staff (whether medical or informatics) and patients, who are often old and sick and have limited knowledge of technology. Others relate to the clinical nature of the encounter: data cannot be taken from patients as part of clinical care unless there is a plan to act on whatever information is prepared. We also note that the plethora of marketing questionnaires makes patients suspicious of surveys: patient trust is hard to gain and easy to lose. Addition of these golden rules to standard approaches to interface design will maximize our ability to obtain data from patients and thus improve communication between patients and clinicians.